Application of Arbuscular Mycorrhizal Fungi and Soil Ameliorant on the Growth of Leucaena leucocephala in Limestone Post-mining Soil Media - Siti Hanna Ghaida; Basuki Wasis; Sri Wilarso Budi (Jurnal Manajemen Hutan Tropika, 2020)
Limestone mining has the potential into environmental damage that involve modify an ecosystem. The attempt that contrived to reduce the disturbances are rehabilitation. This research was conducted to examine the growth response of Leucaena leucocephala inoculated with AMF and soil ameliorant in a limestone post-mining soil. The design used was a split-plot design in a completely randomized design with 3 factors. The first factor was AMF inoculum (Daemonorops draco AMF and MycoSilvi), the second factor was organic fertilizer of compost, and the third factor was inorganic fertilizer. The variables used in this study expressed by height, diameter, biomass, root colonization, and nutrient absorption of the plant. The analysis showed that the combination of MycoSilvi and compost 7.5% gave best result of height, diameter, and biomass, with significantly increased by 962.67%, 899.41% and 1440.67% to control plant. It also gave best result of nutrient uptake N, P, and K, with significantly increased up to 17.64 g plant-1, 2.42 g plant-1, and 18.05 g plant-1. In general, AMF showed a good percentage of root colonization with an average 36.67-86.67%. Further research is needed to determine the response to the growth of seedlings planted in the field.